Perencanaan Strategi Pemasaran Untuk Meningkatkan Loyalitas Pelanggan Pada Penjualan Produk Elektronik - Anggit Dyah Kusumastuti; Annisa Muktining Cahaya; Talitha Sahda Hanifah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study was conducted with the aim of utilizing the SWOT method and Quantitative Strategic Planning Matrix (QSPM) approaches to choose objective marketing strategies to increase customer loyalty towards purchasing electronic products at PT. Electrindo. The data obtained from the previous stage will be re-developed for analysis based on the method to be used, namely: Sales data for the period January - September 2023. Based on the results of the SWOT method analysis that is appropriate for PT. Electrindo. The SWOT analysis provides 5 alternative strategies that can be chosen by the company PT. Electrindo, namely using digital and influencer strategies, using promotion and discount strategies, using product and technology innovation strategies, using email marketing strategies, using traditional strategies and local communities. Regarding the results of the analysis using the QSPM method, among the five alternative strategies, the alternative strategy that is preferred by the company PT. Electrindo is using promotion and discount strategies to increase customer buying interest in electronic products.